COMPLEX RETINAL DETACHMENT IN PHAKIC PATIENTS: Previtrectomy Phacoemulsification Versus Combined Phacovitrectomy. Issue 4 (April 2017) - Tosi, Gian Marco; Balestrazzi, Angelo; Baiocchi, Stefano; Tarantello, Antonio; Cevenini, Gabriele; Marigliani, Davide; Simi, Francesco
Abstract : Purpose: To assess the impact of phacoemulsification performed one week before pars plana vitrectomy versus combined phacovitrectomy on postoperative anterior segment status and final functional and anatomical outcomes in phakic patients affected by complex rhegmatogenous retinal detachment. Methods: The authors retrospectively reviewed the records of 59 phakic patients affected by complex rhegmatogenous retinal detachment. Twenty-nine patients underwent cataract surgery 7 days before vitrectomy (preemptive cataract surgery—Group 1), whereas 30 patients underwent combined phacovitrectomy (Group 2). Preoperative, intraoperative, early- and late-postoperative outcomes were measured and compared. Results: Numbers of previous retinal surgical procedures, nuclear sclerosis grade, proliferative vitreoretinopathy grade, eyes with inferior breaks, surgical time, and ratio of silicone oil/gas tamponade were all similar between the two groups. After surgery, there was less extension of posterior synechia in Group 1. There was no significant difference in fibrin, number of patients with posterior synechia, final intraocular pressure, retinal redetachment rate, final retinal status, or final best-corrected visual acuity. Conclusion: Preemptive cataract surgery was associated with less extensive postoperative posterior synechia, however, its final functional and anatomical outcomes were not significantly different from those of phacovitrectomy. Both approaches were efficacious. Abstract : Previtrectomy cataract surgery was associated with less extensive postoperative posterior synechia, however, its final functional and anatomical outcomes were not significantly different from those of combined phacovitrectomy. Both approaches were efficacious.